A Rare Case of Isolated Congenital Incudostapedial Cholesteatoma - Chung Wui, Loi; Leong Wai, Lee; Ing Ping, Tang (Wolters Kluwer - Medknow, 2025)
Cholesteatoma can be classified as congenital, acquired, and unknown caused. Acquired cholesteatoma is most seen, whereas congenital cholesteatoma is a rare encounter in otorhinolaryngology practice, which mostly arises behind an intact tympanic membrane without any history of ear trauma, infection, or surgery prior. We present a case of 12‑year‑old boy with unilateral hearing loss with no significant otology history or finding, intraoperative noted cholesteatoma in the incudostapedial joint. Postoperatively, the patient recovered well with significant improved hearing over the affected ear.